K вопросу о сленге как главном источнике образования неформальной лексики в австралийском варианте английского языка - Малинка, Я.А.; Татарникова, И.В. (Культура народов Причерноморья, 2013)
Данная статья посвящена изучению явления неформальной лексики как современного
феномена существования австралийского варианта английского языка (AuE). Основным источником
формирования этого особого пласта лексики является сленг. По предварительным результатам
проведённого исследования можно говорить о наличии специфических особенностей австралийского
сленга как стилистически окрашенной лексики, а так же о рекуррентности четырёх способов
образования сленга в AuE, а именно: полное заимствование, заимствование основы, перевод и
фонетическая мимикрия.
Ключевые слова: неформальная лексика, сленг, локально-маркированная лексика, австралийский
вариант английского языка (AuE). Дана стаття присвячена вивченню явища неформальної лексики як сучасного феномена
існування австралійського варіанту англійської мови (AuE). Основним джерелом формування цього
особливого пласта лексики є сленг. За попередніми результатами проведеного дослідження можна
стверджувати про наявність специфічних особливостей австралійського сленгу як стилістично
забарвленої лексики, а також про рекурентність чотирьох способів формування сленгу в AuE, а саме:
повне запозичення, запозичення основи, переклад і фонетична мімікрія.
Ключові слова: неформальна лексика, сленг, локально-маркована лексика, австралійський варіант
англійської мови (AuE). This article focuses on the study of the phenomenon of the informal language as a modern
phenomenon of the existence of the Australian variant of the English language (AuE). The main source of this
particular layer of the vocabulary is a slang.. According to the preliminary results of the conducted research it is
possible to assert the specific features of Australian slang as stylistically marked vocabulary and about the
existence of the recurrence of four ways of slang formation in AuE, namely: full borrowing, borrowing basis,
translation and phonetic mimicry.
The study of different aspects of the functioning of the informal language shows it has a medium-low nature and
it tends to be neutral standard vocabulary. The indicator of the relevance of this topic is the positive dynamics of
the use of the informal language in the colloquial register of AuE and its mass penetration in many activity fields
of native speakers of English. It can be deducted from the results of the research conducted by other researchers,
the informal language has ceased to be perceived solely as a marker of the lower social status of a speaker.
Among the results obtained it is possible to assume that the rhymed structure of collocation segments constitutes
one of the most indicated features of Australian slang. The vast majority of rhymed slangy collocations has
mostly a binary structure and is represented by the combination of words which belong the literary standard. It
has been revealed that the widely spread rhymed variety of slang is an important distinctive feature of slang
functioning on the territory of Australia.
Keywords: informal language, slang, locally-marked vocabulary, the Australian variant of the English language
(AuE).